2016
DOI: 10.1007/s40273-016-0407-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of HPV Vaccination: A Systematic Review of Modelling Approaches

Abstract: Abstract:Background: A large number of economic evaluations have been published that assess alternative possible HPV vaccination strategies. Understanding differences in the modelling methodologies used in these studies is important to assess the accuracy, comparability and generalisability of their results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It is important to note that Gardasil-9 has not yet been approved for use in subjects who have received three doses of Gardasil or Cervarix ( 214 ). Moreover, Gardasil-9 is expected to be more cost-effective than HPV vaccines currently in use ( 215 , 216 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…It is important to note that Gardasil-9 has not yet been approved for use in subjects who have received three doses of Gardasil or Cervarix ( 214 ). Moreover, Gardasil-9 is expected to be more cost-effective than HPV vaccines currently in use ( 215 , 216 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…Recently, there has been a growing interest in understanding the influence of choices around model structure and parameters on the results from the model [4][5][6]. Frederix et al showed that differences in the choice of parameters in CE analyses comparing tamoxifen and anastrozole for the treatment of breast cancer were associated with major differences in CE results despite using the same clinical trial for TEs [4].…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness of routine female adolescent human papillomavirus (HPV) vaccination and other strategies (e.g., vaccinating males as well) has been extensively studied for many high-income countries (e.g., the UK, Australia, Canada) as well as middle- and low-income countries (e.g., Malaysia, Brazil, Peru) [ 1 ]. The consensus among these studies is that routine female adolescent HPV vaccination is cost-effective.…”
Section: Introductionmentioning
confidence: 99%